2022
DOI: 10.1155/2022/9707278
|View full text |Cite
|
Sign up to set email alerts
|

Antitoxic Effects of Curcumin against Obesity-Induced Multi-Organs’ Biochemical and Histopathological Abnormalities in an Animal Model

Abstract: Background. Obesity is a significant public health problem that is characterized by an increase in oxidative stress and enhanced inflammatory responses associated with immune cell invasion of adipose tissues. This study assessed several biochemical abnormalities, apoptosis, oxidative stress status, and associated histological changes in the liver, duodenum, and heart brought on by high-fat diet-induced obesity in rats. It also assessed the mechanistic benefits of curcumin in reversing these inflammatory, metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…Hassan et al 36 who conducted a recent mechanistic study concluded curcumin does have the ability to exert potent antitoxic, anti-oxidant, tissue-protective, and anti-obesity effects, hence they recommended curcumin be added to various dietary regimens to prevent or delay organ dysfunction among obese people. Tsuda et al 37 similarly agree that curcumin has anti-obesity/anti-adipogenic and anti-diabetes biological properties among others, as also observed by Labban et al 38 and can be seen to have a high probability of preventing or reducing the magnitude of various obesity states through well defined biochemical signaling pathways and others that may be active even on preadipocytes, 39 as well as in reversing or modulating age and obesity associated metabolic diseases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hassan et al 36 who conducted a recent mechanistic study concluded curcumin does have the ability to exert potent antitoxic, anti-oxidant, tissue-protective, and anti-obesity effects, hence they recommended curcumin be added to various dietary regimens to prevent or delay organ dysfunction among obese people. Tsuda et al 37 similarly agree that curcumin has anti-obesity/anti-adipogenic and anti-diabetes biological properties among others, as also observed by Labban et al 38 and can be seen to have a high probability of preventing or reducing the magnitude of various obesity states through well defined biochemical signaling pathways and others that may be active even on preadipocytes, 39 as well as in reversing or modulating age and obesity associated metabolic diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Schematic representation of possible benefits of curcumin supplementation in cases of intractable obesity or those at risk for obesity. 4,33,[35][36][37]40,42,56,57…”
Section: Figurementioning
confidence: 99%
“…Based on its good dispersibility, it can enter the interior of bacteria and react with their enzymatic and biofilm systems. [27][28][29] The lipids of cell membranes have hydrophobic alkyl chains and hydrophilic polar groups, while curcumin, which has a phenolic ester structure, is not readily soluble in water and has hydrophilic groups and hydrophobic alkyl chains too, so it can dynamically reside in biological membranes and directly and rapidly disrupt the membrane structure and interfere with the energy metabolism of cells and organelles. 30 Because it is located in the cell membrane, it is hard to be decomposed by microbial enzymes, so it can achieve a lasting effect of inhibiting bacterial activity.…”
Section: Bacterial Inhibition Effect Investigationmentioning
confidence: 99%
“…Antioxidants 2023, 12, x FOR PEER REVIEW 2 of 33 has been found to prevent organ dysfunction and is recommended as a dietary supplement for obese individuals [8]. Related to counteracting the oncogenic stress management system, curcumin not only causes the death of different Kaposi's sarcoma-associated herpes virus KSHV-positive cells but also obstructs the development of KSHV-infected cells [9].…”
Section: Overview Of Curcumin 21 Biological Activities Of Curcuminmentioning
confidence: 99%
“…Curcumin has shown promise in mitigating the adverse effects of combatting neurodegenerative disorders, making it effective in the treatment of Alzheimer’s disease [ 7 ]. Moreover, curcumin has been found to prevent organ dysfunction and is recommended as a dietary supplement for obese individuals [ 8 ]. Related to counteracting the oncogenic stress management system, curcumin not only causes the death of different Kaposi’s sarcoma-associated herpes virus KSHV-positive cells but also obstructs the development of KSHV-infected cells [ 9 ].…”
Section: Introductionmentioning
confidence: 99%